Pembuatan Website sebagai Media Informasi Desa Wisata Nagari Sungai Batang - Rokhayati, Yeni; Pamungkas, Daniel Sutopo; Santiputri, Metta; Sibagariang, Swono; Triwinarko, Andy; Thohari, Ahmad Hamim; Handayani, Siskha; Ardi, Noper (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
Nagari Sungai Batang, known as the birthplace of the religious figure Buya Hamka, is a culturally rich village with great tourism potential. However, it currently lacks an official website, and information about the village is only available on external news portals or the Ministry of Tourism and Creative Economy website. To enhance its visibility and accessibility, this community service project aimed to develop a dedicated website for Nagari Sungai Batang as a medium of information and promotion. This activity was part of a collaborative program between Politeknik Negeri Batam and Politeknik Negeri Padang, where the former developed the website while the latter created the information system. The website was developed using the Waterfall model, covering stages from requirements analysis to implementation and testing. Evaluation was conducted using Alpha-Beta testing, involving both developer and user environments. After completion, the team delivered the website and conducted user training on content management. The result showed that the website effectively served as an information and promotional medium, achieving a user satisfaction rate of 96%.